First-in-man trial of b3-adrenoreceptor agonist treatment in chronic heart failure – impact on diastolic function. (3rd October 2022) - Bahrami, H; Hasselbalch, R; Soeholm, H; Thomsen, J; Soegaard, M; Kofoed, K; Valeur, N; Boesgaard, S; Fry, N; Moeller, J; Raja, A; Koeber, L; et al.
Abstract: Background: Diastolic dysfunction (DD) in heart failure (HF) is associated with increased myocardial cytosolic calcium, and calcium-efflux via the sodium-calcium-exchanger depends on the sodium gradient. Beta-3-adrenoceptor (β3-AR)-agonist lowers cytosolic sodium and has been shown to reverse organ congestion. Purpose: To assess whether β3-AR-agonist treatment improves DD. Methods: In a first-in-man randomized controlled, double-blind trial, we assigned 70 patients with HF with reduced ejection fraction (HFrEF) (NYHA II–III) and LVEF <40% to receive mirabegron (300 mg/day) or placebo for 6 months, in addition to recommended HF-therapy. Patients were assessed with echocardiography and cardiac computed tomography (CCT) at baseline and follow-up. DD was graded according to the current American/European guidelines. Results: Baseline and follow-up echocardiographic data were available in 57 patients (59±11 years, 88% male, 49% ischemic heart disease). Baseline LVEF was 34%±8%. No significant change in DD grade was found between the groups at follow-up, p=0.72. Neither was there any clinical differences in any singular diastolic parameters within or between groups by echocardiography (E/e' placebo: 13.3±6.9 to 12.6±5.1, p=0.19 vs. mirabegron: 12.0±5.7 to 12.8±7.9, p=0.67, mean difference 1.12 [95% CI −1.68 to 4.3], p=0.37), or CCT (left atrial max volume index: between group mean difference 0.2 [95% CI −6.2 to 5.6] ml/m 2, p=0.91). Conclusions: In patients with HFrEF, no improvement nor worsening in DD gradings or singular diastolic parameters after β3-AR stimulation compared to placebo were identified. The findings add to previous literature questioning the role of impaired Na+-Ca2+ mediated Ca2+ export as a major culprit in DD. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): The Heart Centre Research Foundation, RigshospitaletThe Novo Nordic Foundation